Increasing use of 'party drugs' in people living with HIV on antiretrovirals: a concern for patient safety. (24th August 2015) - Bracchi, Margherita; Stuart, David; Castles, Richard; Khoo, Saye; Back, David; Boffito, Marta
Abstract : Use of 'party drugs', a particular set of recreational drugs used in the context of 'ChemSex', is frequent among MSM living with HIV. A recently published observational study showed that more than half of HIV-infected MSM interviewed reported use of illicit substances in the previous 3 months, with frequent concomitant use of three or more drugs. These substances are a combination of 'club drugs' (methylenedioxymethamphetamine, gamma-hydroxybutyrate, ketamine, benzodiazepine) and drugs that are more specifically used in a sexualized context (methamphetamine, mephedrone, poppers and erectile dysfunction agents). Although formal data on pharmacokinetic or pharmacodynamic interactions between recreational drugs and antiretroviral agents are lacking, information regarding potentially toxic interactions can be theorized or sometimes conclusions may be drawn from case studies and cohort observational studies. However, the risk of coadministering party drugs and antiretrovirals should not be overestimated. The major risk for a drug–drug interaction is when using ritonavir-boosting or cobicistat-boosting agents, and maybe some nonnucleoside reverse transcriptase inhibitors. Knowledge of the metabolic pathways of 'party drugs' may help in advising patients on which illicit substances have a high potential for drug–drug interactions, as this is not the case for all.